PENERAPAN KONSELING KELOMPOK BERBASIS TEORI IBNU SINA DALAM MENGONTROL KECEMASAN SANTRI - Dina Panisa; Nur Hermatasiyah; Aceng Akhmad Munanzdar Alkafi Billah (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
Anxiety is a natural emotional response to certain situations; however, it can become maladaptive when it arises excessively and interferes with students’ learning activities and social life. Group counseling utilizes group dynamics as a medium for sharing experiences, providing emotional support, and fostering collaborative learning in addressing psychological problems. This study aims to describe the implementation of group counseling based on the theory of Ibnu Sina in controlling students’ anxiety. Ibn Sina’s theory is used as a conceptual foundation emphasizing the balance between the soul, intellect, and body, as well as the importance of managing thoughts and emotions in maintaining mental health. This research employs a qualitative approach with a descriptive research design. The research subjects are Qur’an-memorizing students who experience anxiety. Data were collected through interviews, observations, and documentation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results indicate that prior to participating in group counseling, students exhibited symptoms of anxiety such as excessive worry, difficulty concentrating, and emotional tension.